ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PT FKS FOOD SEJAHTERA TBK PERIODE 2022-2023 - Mochammad Luthfi Windikusuma, Noor; Noor Azizah, Reva; Wiayanti, Riesta (Sekolah Tinggi Ilmu Ekonomi GICI, 2025)
This study aims to assess the financial condition and performance of PT FKS Food Sejahtera Tbk for the years 2022-2023 by using various financial ratios, namely the Liquidity Ratio, Solvency Ratio, Activity Ratio, and Profitability Ratio. The data used in this research are secondary data obtained from the Indonesia Stock Exchange (IDX). The analysis of financial ratios reveals several key findings: The liquidity ratio shows that the company is struggling to meet its short-term obligations. The solvency ratio indicates that the company funds its activities more through debt than equity. The activity ratio shows that the company has effectively optimized its resources to support sales and manage fixed assets and investments. However, the profitability ratio indicates that the company is facing difficulties in generating optimal profits from its equity